From practice to competition : a coach's guide for designing training sessions to improve the transfer of learning / Gibson Darden, Sandra Wilson. - Darden, Gibson F. (Gibson Fisher); Wilson, Sandra, 1965- (Professional development in sport coaching., 2023)
Practice may arguably be the most important predictive factor of athlete success in a sport. Designing and conducting effective practice sessions should therefore be an essential element of all coach education and development efforts. In 'From Practice to Competition', Gibson Darden and Sandra Wilson provide practical, research-based recommendations for coaches to help them get the most out of their athletes at every practice. Easily transferrable across a variety of sports, this guide explores and applies 'transfer of learning' concepts that coaches can use to better design and structure their training sessions.